Microstructural characterization and wear properties of in situ AlB2–reinforced Al–4Cu metal matrix composite. (May 2016) - Ficici, Ferit; Koksal, Sakip
Aluminium matrix composites have been extensively studied for several decades due to the potential advantages over classical low-density materials. Low-density composites can offer high wear and corrosion resistance, high strength, and favorable thermal electrical properties that attract the attention of various industries such as aerospace and automotive. This study investigates the dry sliding wear behavior of AlB2 –Al–4Cu composites with 5, 10, 20, and 30% weight reinforcement. In situ developed AlB2 flakes were incorporated as the reinforcing compound in the Al–4Cu matrix. The composite samples were tested against a steel disk using a pin-on-disk wear rig. The effect of reinforcement ratio, applied load, sliding velocity on the wear rate and friction coefficient of the composite samples was investigated. In addition, the worn surfaces have been characterized in terms of wear patterns. Compared to the matrix alloy, composite samples exhibited better wear resistance and lower friction coefficient to varying degrees of magnitudes.